2008
DOI: 10.1124/mol.108.052399
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Resonance Energy Transfer Analysis of α2a-Adrenergic Receptor Activation Reveals Distinct Agonist-Specific Conformational Changes

Abstract: Several lines of evidence suggest that G-protein-coupled receptors can adopt different active conformations, but their direct demonstration in intact cells is still missing. Using a fluorescence resonance energy transfer (FRET)-based approach we studied conformational changes in ␣ 2A -adrenergic receptors in intact cells. The receptors were C-terminally labeled with cyan fluorescent protein and with fluorescein arsenical hairpin binder at different sites in the third intracellular loop: N-terminally close to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 41 publications
4
66
1
Order By: Relevance
“…In recent years it became obvious that AT 1 R and most probably also other GPCRs possess more than one active or inactive receptor conformation in analogy to the different states of ion channels. In line with this notion, different partial agonists were shown to induce several distinct active receptor conformations (116). In the performance of bioluminescence resonance energy transfer (BRET) experiments, it was demonstrated that membrane stretch favors an active AT 1 R conformation that is recognized by ␤-arrestin (62), an observation that was recently verified by Rakesh et al (81) in performing intermolecular fluorescence resonance energy transfer (FRET) experiments.…”
Section: Gpcrs As Mechanosensorsmentioning
confidence: 59%
“…In recent years it became obvious that AT 1 R and most probably also other GPCRs possess more than one active or inactive receptor conformation in analogy to the different states of ion channels. In line with this notion, different partial agonists were shown to induce several distinct active receptor conformations (116). In the performance of bioluminescence resonance energy transfer (BRET) experiments, it was demonstrated that membrane stretch favors an active AT 1 R conformation that is recognized by ␤-arrestin (62), an observation that was recently verified by Rakesh et al (81) in performing intermolecular fluorescence resonance energy transfer (FRET) experiments.…”
Section: Gpcrs As Mechanosensorsmentioning
confidence: 59%
“…However, once this has happened, the protein states that follow resemble those formed in other GPCRs; in the case of rhodopsin, the socalled Meta states all contain the all-trans-retinal agonist bound by a deprotonated retinal Schiff base, but are distinguished by specific arrangements of crucial amino acids and their connecting hydrogen bonds. Corresponding R and R* conformational states can be delineated for other GPCRs and strongly suggest the presence of multiple active forms of GPCRs (Zürn et al, 2009;Nygaard et al, 2013;Manglik et al, 2015).…”
Section: Temporal Aspects-kinetics Along the Signaling Chainmentioning
confidence: 99%
“…Different GPCR conformations are causally related to different signaling activity states (3,10,11). Furthermore, differences between activated conformations depend on particular interacting ligands, and they are probably involved in determination of G-protein subtype preferences (12)(13)(14)(15)(16)(17). The previously published GPCR structures of inactive receptor conformations (for reviews, see Refs.…”
mentioning
confidence: 99%